Review on Medical Waste Management (International Journal of Innovative Research in Engineering & Management, 2023)
Medical wastewater is analysed in this  chapter, along with prevalent causes, governing  legislation, and recycling and storage methods. Medical  waste legislation exists in many developed countries, yet,  there is no guideline on something that may and could be  categorised as infectious. Selecting medical waste has  grown inefficient leading to a shortage of clarity,  culminating in a growth in the amount of garbage that  may be cleansed for infections, which itself is usually  done by incineration. According to this study it  identifying garbage as hazardous leads to greater  production of the waste. More investigation is necessary,  given the tendency of increasing medical waste output  with growing world GDP, and greater medical  professional education and accessible medical generated  waste sorting are significant possibilities for reduction  and composting in healthcare institutions, according the  paper.
Keywords: Healthcare; MedicalWaste; InfectiounWaste Management; SeparateCollection